Highly efficient underwater acoustic absorber designed by filled-microperforated plate-like structure: Aging and life prediction - Jingjing Nan; Lingjie Yu; Mingjuan Du; Jiaguang Meng; Zijing Dong; Menghe Miao; Chao Zhi (Polymer Testing, 2023)
The underwater sound absorption material for submarines should fulfill the demand for remarkable performance in medium-low frequency sound absorption at low thicknesses. Hence, in this paper, the innovative “filled-microperforated plate-like” (F-MPPL) structure was introduced to the hollow microballoons filled underwater sound absorption composite (HBF composite) using the tailor-made 3D spacer fabric. The test results show remarkable mechanical properties with a compression strength and compression modulus of 2256 KPa and 14.6 MPa for the new type of F-MPPL composite, respectively. In addition, the peak sound absorption coefficient of the F-MPPL composite reaches 0.77 at just 7.5 mm thickness based on the resonant sound absorption characteristic introduced by the F-MPPL structure. Moreover, the study investigated the effects of seawater aging on the F-MPPL composite and found that while there was a decrease in compression strength and average sound absorption coefficient, the degradation of the F-MPPL composite was significantly smaller than the HBF composite due to the inhibitory effect of spacer yarns on pore expansion. Finally, this study proposed the method of using compression strength to predict the long-term life of the F-MPPL composite under seawater aging, and a 60% retention rate after 20 months was displayed.